A molecular framework for understanding the phylogeny of Spiranthes (Orchidaceae), a cosmopolitan genus with a North American center of diversity1. Issue 9 (1st September 2014) - Dueck, Lucy A.; Aygoren, Deniz; Cameron, Kenneth M.
Abstract : Premise of the study: Spiranthes is a genus of small terrestrial orchids that are most diverse in North America, yet unusually cosmopolitan, including many of conservation concern. Taxonomy based on morphology alone is problematic, but molecular evidence could help resolve evolutionary relationships within the genus. The phylogeny of Spiranthes was reconstructed to evaluate these patterns, particularly among North American and Old World lineages, determine the systematic value of chromosome numbers and phenology, consider aspects of historical biogeography, and provide evidence for the taxonomic status of vulnerable species. Methods: DNA sequences were produced from 219 samples representing 30 Spiranthes taxa plus one outgroup. Both parsimony and Bayesian inference analyses were applied to individual and combined data matrices generated for nuclear (nrITS) and plastid ( trnL, trnS‐G, matK ) regions. Key results: Two major clades were recovered. One contains primarily summer‐blooming species from western North America with haploid chromosome number of n = 22. The other clade (largely n = 15) contains midwestern and eastern North American species varying in phenology, although most autumn‐flowering taxa within it are monophyletic. Whereas an Old World subclade is embedded within the tree, derived from New World ancestors, no genetic differentiation was found between trans‐Atlantic specimens of S. romanzoffiana . Most species for which multiple individuals were sampled reflect monophyly in the combined gene tree (including S. lucida positioned on an unusually long branch), but some demonstrate dubious taxonomic status. Conclusions: This is the most complete phylogenetic reconstruction of Spiranthes published to date and is likely to influence future taxonomic decisions, with important implications for conservation of several threatened orchids. Our discoveries about species distributed outside North America offer important evidence for repeated long‐distance dispersal, often coupled with subsequent speciation—an uncommon phenomenon in Orchidaceae.